A Study for the Access to a Semi-synthetic Regioisomer of Natural Fucosylated Chondroitin Sulfate with Fucosyl Branches on N-acetyl-Galactosamine Units - Giulia Vessella; Serena Traboni; Anna V. A. Pirozzi; Antonio Laezza; Alfonso Iadonisi; Chiara Schiraldi; Emiliano Bedini (Marine Drugs, 2019)
Fucosylated chondroitin sulfate (fCS) is a glycosaminoglycan found up to now exclusively in the body wall of sea cucumbers. It shows several interesting activities, with the anticoagulant and antithrombotic as the most attractive ones. Its different mechanism of action on the blood coagulation cascade with respect to heparin and the retention of its activity by oral administration make fCS a very promising anticoagulant drug candidate for heparin replacement. Nonetheless, its typically heterogeneous structure, the detection of some adverse effects and the preference for new drugs not sourced from animal tissues, explain how mandatory is to open an access to safer and less heterogeneous non-natural fCS species. Here we contribute to this aim by investigating a suitable chemical strategy to obtain a regioisomer of the natural fCS polysaccharide, with sulfated l-fucosyl branches placed at position O-6 of N-acetyl-d-galactosamine (GalNAc) units instead of O-3 of d-glucuronic acid (GlcA) ones, as in natural fCSs. This strategy is based on the structural modification of a microbial sourced chondroitin polysaccharide by regioselective insertion of fucosyl branches and sulfate groups on its polymeric structure. A preliminary in vitro evaluation of the anticoagulant activity of three of such semi-synthetic fCS analogues is also reported.